Integrasi Hermeneutika dan Ushul Fiqh dalam Istinbath Hukum Islam - Khoirul Anwar; Nihayatut Tasliyah (Jurnal Multidisiplin Ibrahimy, 2024)
The science of ushul fiqh is one of the scientific tools in exploring (Istinbath) Islamic law. The primary material is legal sources, linguistic rules, and maqashid al-syari'ah. In the same way, hermeneutics is a science of interpretation that emphasizes aspects of the text, the author of the text, and the reader of the text. With these three tools, the science of hermeneutics can be combined to explore Islamic law to obtain comprehensive, methodologically accountable, and relevant to current developments. This way, Islamic law is not left behind but can answer contemporary problems.